THE PARTICIPATION OF SCOUTS AT BATTLES FROM DOBROGEA (SEPTEMBER – OCTOBER 1916). THE BATTLE FROM AMZACEA - PĂTRAŞCU Dumitru-Valentin (Journal of Industrial Design and Engineering Graphics, 2014)
The reserch of the present study was based on original documents from the document collection of the “Alexandru Ştefulescu” Museum of Gorj County in Târgu-Jiu in regard to the scouting in Romania. This study was dedicated to the anniversary of one hundred years of scouting in Romania and also to the participation of scouts Gheorghe and Mihail Cristescu, nephews of lawyer Constantin Dumitru Brătuianu from Ţicleni, Gorj county, at the battle of Amzacea (the southern part of Dobroudja region) in the autumn of 1916.